Assessment of the knowledge, attitudes, and practices toward human tuberculosis amongst rural communities in Chad - Didi, Lamireou; Abakar, Mahamat Fayiz; Bongo Naré Richard, Ngandolo; Djané, Adou; Kessely, Hamit; Issaka, Yaya; Diagbouba, Serge; Adrien Marie Gaston, Belem; Zinsstag, Jakob; Bonfoh, Bassirou; Dürr, Salome (Frontiers in Veterinary Science, 2024)
Introduction Tuberculosis (TB) is an infectious zoonotic disease caused by bacteria belonging to the Mycobacterium tuberculosis complex. In sub-Saharan African countries such as Chad, TB is endemic and causes a high burden on humans and animals through morbidity, mortality, and reduced productivity in livestock. To effectively prevent and control the disease, strong coordination between policymakers, health and veterinary services, civil society organizations, and communities is needed. It also requires an understanding of the knowledge the communities have regarding TB. However, such knowledge is under-investigated, especially in rural areas. How knowledge affects people's attitudes and practices is also unclear. The main objective of this study was to investigate the knowledge, attitudes, and practices (KAP) of Chadian rural communities to better involve them in TB surveillance programs. Methods A survey was conducted in 2021 in five rural health centers. Face-to-face interviews were conducted with persons suspected of having TB, and data on KAP were recorded and analyzed. Results In total, 139 participants were enrolled. Overall, the knowledge and attitude of the participants were found to be good to moderate, with 126 (90.6%) and 97 (69.7%) having good knowledge and attitude, respectively. However, their practices were found to be rather weak, with only 40 (28.7%) participants having good practices. Men were found to have good knowledge about the disease significantly more often than women. Poor attitude was significantly associated with a mobile lifestyle compared to settled lifestyles and with farmers (mainly engaged in agriculture) compared to breeders (livestock keepers). Poor health practices were associated more with men than women and with settled lifestyles compared to a mobile lifestyle. Good practices were found to be in line with good knowledge and good attitudes; however, in the analyses, the association was not significant [OR knowledge = 5.83 (95% C.I. 0.6842.83), p = 0.112; OR attitude = 2.09 (95% C.I. 0.875.04), p = 0.100]. Furthermore, attitude was not associated with knowledge [OR = 1.03 (95% C.I. 0.303.55), p = 0.964]. Discussion and conclusion Our study highlights the need for targeted sensitization and awareness campaigns for communities with poor knowledge and attitudes regarding TB. These campaigns should also include practical training to increase the level of good practice rather than simply providing knowledge.